European views of Turkish foreign policy - (:unkn) unknown (My University, 2013)
This article examines how the European elite views new parameters of Turkey's increasing activism in the Middle East with special emphasis on county's role in the Middle East in the context of claims of shift of axis on ideological grounds and Turkey's relations with the EU, Iran and Israel. It is demonstrated the emerging European perception among policy analysts and scholars regarding Turkish foreign policy is generally positive, and recent changes do not mean a shift in country's foreign policy orientation. Turkey is still perceived to be part of the Western alliance, but it is now seen more confident in taking initiatives and more eager to develop a regional approach.